The effect of financial constraints on inventory holdings - Emil Bustos (Research Institute of Industrial Economics (IFN), 2023)
This paper investigates the impact of financial constraints on firms' inventory holdings, an area of significant interest given that inventories are volatile over the business cycle. I use detailed data on Swedish firms' balance sheets, income statements, and credit scores. I employ a regression discontinuity design and a difference-in-differences analysis to examine the causal effects of financial constraints on inventory management. Firms with relaxed financing constraints increase their inventories by 20% when they get a better credit score, yet there is no robust effect on inventories relative to firm size. This study offers new insights into the influence of financial constraints on firms' inventory strategies amidst changing economic conditions.
Keywords: D22; D25; G32; G32; 330; Financial Constraints; Risk Management; Inventories; Credit Scores; Private Firms